Cerebrospinal fluid and serum MHPG improve Alzheimer's disease versus dementia with Lewy bodies differential diagnosis. Issue 1 (5th February 2018) - Janssens, Jana; Vermeiren, Yannick; Fransen, Erik; Aerts, Tony; Van Dam, Debby; Engelborghs, Sebastiaan; De Deyn, Peter P.
Abstract: Introduction: Given the challenges concerning the differential diagnosis of dementia, we investigated the possible added value of monoaminergic compounds to the standard cerebrospinal fluid (CSF) Alzheimer's disease (AD) biomarkers. Particularly, regarding the AD versus dementia with Lewy bodies (DLB) comparison, monoamines or their metabolites might have added discriminative value as there is a more severe neuropathological burden in the locus coeruleus of DLB patients, the principal site of noradrenaline synthesis. Methods: We applied enzyme‐linked immunosorbent assay (ELISA) to analyze CSF amyloid β peptide of 42 amino acids, total tau, and tau phosphorylated at threonine 181, in patients with AD, frontotemporal dementia, DLB/Parkinson's disease dementia, and controls. Reversed‐phase high‐performance liquid chromatography with electrochemical detection was implemented to study monoamine and metabolite levels in CSF and serum. Stepwise forward conditional logistic regression and receiver operating characteristic (ROC) curve analyses were performed to assess the diagnostic accuracy of these newly fitted models containing the most discriminative indicators of disease status. Results: Most significant differences in CSF and serum were confined to the noradrenergic system. More specifically, CSF 3‐methoxy‐4‐hydroxyphenylglycol (MHPG) levels were higher, whereas serum MHPG levels were lower, in DLB patients compared with all other groups. Addition of CSF and serum MHPG levels to the CSF AD biomarker panel significantly increased diagnostic accuracy between DLB/Parkinson's disease dementia and AD. Interestingly, a model only including CSF and serum MHPG without the classic AD biomarker panel reached similar area under the curve values. Discussion: We hypothesize that varying degrees of neuronal loss in the locus coeruleus of DLB/Parkinson's disease dementia versus AD patients result in differentially altered MHPG levels, making this metabolite a valuable biomarker.